Agrobiological parameters of various varieties and hybrids of sweet sorghum - В. В. Любич (Ukrainian Institute for Plant Variety Examination, 2021)
Purpose. To reveal the features of agrobiological parameters formation of sweet sorghum various varieties and hybrids in the conditions of the Right-Bank Forest-Steppe of Ukraine.